2017
DOI: 10.1016/j.jcmg.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Precision Phenotyping in Heart Failure and Pattern Clustering of Ultrasound Data for the Assessment of Diastolic Dysfunction

Abstract: Tracking deformation of the left-sided cardiac chambers from routine cardiac ultrasound images provides accurate information for Doppler-independent phenotypic characterization of LV diastolic function and noninvasive assessment of LV filling pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 28 publications
2
47
0
2
Order By: Relevance
“…Our findings support the hypothesis that HFpEF could be a result of lower subendocardial contractility linked with increased subepicardial contractility (Sengupta and Narula, 2008; Shah and Solomon, 2012; Omar et al, 2016, 2017). When subendocardial contractility was zero, LVEF decreased by 23.9% (Table 2: 53.2% in scenario 1 vs. 40.5% in scenario 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings support the hypothesis that HFpEF could be a result of lower subendocardial contractility linked with increased subepicardial contractility (Sengupta and Narula, 2008; Shah and Solomon, 2012; Omar et al, 2016, 2017). When subendocardial contractility was zero, LVEF decreased by 23.9% (Table 2: 53.2% in scenario 1 vs. 40.5% in scenario 2).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have suggested that HFpEF is associated with transmural changes in myocardial deformation (Shah and Solomon, 2012; Omar et al, 2016, 2017). Understanding the transmural variations in left ventricular (LV) mechanics associated with HFpEF may offer pathophysiological insights for developing potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Making sense of all this information is a challenge that can likely be met by machine learning. Recent studies suggest that it may be useful for diagnosis and for defining pathophysiology, 15 , 295 , 296 but long‐term studies in large populations are needed to unravel which features best predict clinical outcomes and responses to treatment. Molecular phenotyping for a better identification of distinct HFpEF phenotypes is emerging and may also help to develop targeted therapies.…”
Section: Calculating and Interpreting The Hfa–peff Scorementioning
confidence: 99%
“…Additional diagnostic criteria for HFpEF have been published, including one scoring system, but they differ in echocardiographic cut‐off values, the role of comorbidities, the inclusion of biomarkers, the role of invasive haemodynamic assessment, and the role of exercise stress testing , 4 , 6–8 . Understanding of the pathophysiology of HFpEF has advanced, 9–13 diagnostic options have evolved, 14–17 and this novel information needs to be integrated into a new comprehensive diagnostic algorithm for suspected HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…What we need are new methods to integrate all the information from sophisticated non‐invasive diagnostic tests at rest and during exercise, and to identify from large prospective studies which tools are the best for diagnosis, prognosis, and monitoring; they may be different. The application of machine learning to this field is one way in which we might achieve these results …”
mentioning
confidence: 99%